Studies of Pricing in the New Economic Sociology: Premises and Prospects - Елена Сергеевна Бердышева (Journal of Economic Sociology, 2010)
Economic sociologists demonstrate an increasing interest to the issues of pricing in the consumer goods markets. This paper presents a systemiс overview of studies in economic sociology on pricing. It relates new research to the classical sociological concepts and indicate key research problems for the new economic sociology in the ﬁ eld.